Pengukuran Kinerja K3 dalam Pemakaian Alat Pelindung Diri (APD) PT. XYZ - Muhammad Irfan Setiawan; Wahyudin Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Occupational safety and health (K3) is one of the important factors in the smooth running of the product so that the K3 program must be implemented in the company and not just a discourse. Work accidents are accidents that occur in the work environment which can occur due to unsafe working conditions or due to human error. This type of research is a qualitative research with an observational approach and in-depth interviews. The company is also still negligent in terms of fulfilling security facilities, such as providing good, correct and easy-to-reach signs. PPE that is still not fully met. So the company must immediately complete all of them in order to achieve zero accident. The application of K3 at PT. XYZ is still not considered optimal. To achieve zero accident, PT. XYZ must carry out good K3 planning and implementation in accordance with proper procedures.